Chart of the Pribiloff Islands, Bering Sea, Alaska 1875 / drawn by H. Lindenkohl (Washington, D.C. : United States Coast Survey, 1875)
Relief shown by hachures. Depths shown by soundings. Includes note. "Issued in July 1875, C.P. Patterson, Superintendent. Verified by J.E. Hilgard, Assist. in charge of Office." North oriented slightly to the right Grayscale 1:660,000